Tri(n-butyl)phosphine-promoted domino reaction for the efficient construction of spiro[cyclohexane-1,3'-indolines] and spiro[indoline-3,2'-furan-3',3''-indolines] - Zheng, Hui; Han, Ying; Sun, Jing; Yan, Chao-Guo (Beilstein Journal of Organic Chemistry, 2022)
The tri(n-butyl)phosphine-catalyzed reaction of isatylidene malononitriles and bis-chalcones in chloroform at 65 °C afforded functionalized spiro[cyclohexane-1,3'-indolines] in good yields and with good diastereoselectivity. On the other hand, the tri(n-butyl)phosphine-catalyzed reaction of 3-(ethoxycarbonylmethylene)oxindoles and bis-chalcones gave functionalized spiro[cyclohexane-1,3'-indolines] with different regioselectivity. Additionally, the tri(n-butyl)phosphine-promoted domino annulation reaction of isatins and ethyl isatylidene cyanoacetates produced spiro[indoline-3,2'-furan-3',3''-indolines] in satisfactory yields.
Keywords: isatin; spiro[cyclohexane-1,3'-indoline]; spiro[indoline-3,2'-furan-3',3''-indoline]; spirooxindole; tri(n-butyl)phosphine

(untitled) - Williams, R. M.; Cox, R. J. (Acc. Chem. Res., 2003)

(untitled) - Dounay, A. B.; Overman, L. E. (Chem. Rev., 2003)

(untitled) - Santos, M. M. M. (Tetrahedron, 2014)

(untitled) - Yu, B.; Yu, D.-Q.; Liu, H.-M. (Eur. J. Med. Chem., 2015)

(untitled) - Ye, N.; Chen, H.; Wold, E. A.; Shi, P.-Y.; Zhou, J. (ACS Infect. Dis., 2016)

(untitled) - Kotha, S.; Deb, A. C.; Lahiri, K.; Manivannan, E. (Synthesis, 2009)

(untitled) - Trost, B. M.; Brennan, M. K. (Synthesis, 2009)

(untitled) - Ball-Jones, N. R.; Badillo, J. J.; Franz, A. K. (Org. Biomol. Chem., 2012)

(untitled) - Singh, G. S.; Desta, Z. Y. (Chem. Rev., 2012)

(untitled) - Liu, Y.; Wang, H.; Wan, J. (Asian J. Org. Chem., 2013)

(untitled) - Cao, Z.-Y.; Wang, Y.-H.; Zeng, X.-P.; Zhou, J. (Tetrahedron Lett., 2014)

(untitled) - Cheng, D.; Ishihara, Y.; Tan, B.; Barbas, C. F., III (ACS Catal., 2014)

(untitled) - Pavlovska, T. L.; Redkin, R. G.; Lipson, V. V.; Atamanuk, D. V. (Mol. Diversity, 2016)

(untitled) - Bencivenni, G.; Wu, L.-Y.; Mazzanti, A.; Giannichi, B.; Pesciaioli, F.; Song, M.-P.; Bartoli, G.; Melchiorre, P. (Angew. Chem., Int. Ed., 2009)

(untitled) - Chen, G.-S.; Fang, Y.-B.; Ren, Z.; Tian, X.; Liu, Y.-L. (Org. Chem. Front., 2021)

(untitled) - Balha, M.; Mondal, B.; Pan, S. C. (Org. Biomol. Chem., 2019)

(untitled) - Zhang, C.; Lu, X. (J. Org. Chem., 1995)

(untitled) - Lu, X.; Zhang, C.; Xu, Z. (Acc. Chem. Res., 2001)

(untitled) - Methot, J. L.; Roush, W. R. (Adv. Synth. Catal., 2004)

(untitled) - Wei, Y.; Shi, M. (Acc. Chem. Res., 2010)

(untitled) - Guo, H.; Fan, Y. C.; Sun, Z.; Wu, Y.; Kwon, O. (Chem. Rev., 2018)

(untitled) - Ye, L.-W.; Zhou, J.; Tang, Y. (Chem. Soc. Rev., 2008)

(untitled) - Cowen, B. J.; Miller, S. J. (Chem. Soc. Rev., 2009)

(untitled) - Zhou, R.; Liu, R.; Li, R.; He, Z. (Chin. J. Org. Chem., 2014)

(untitled) - Xie, P.; Huang, Y. (Org. Biomol. Chem., 2015)

(untitled) - Zhou, R.; He, Z. (Eur. J. Org. Chem., 2016)

(untitled) - Wei, Y.; Shi, M. (Org. Chem. Front., 2017)

(untitled) - Karanam, P.; Reddy, G. M.; Koppolu, S. R.; Lin, W. (Tetrahedron Lett., 2018)

(untitled) - Tan, B.; Candeias, N. R.; Barbas, C. F., III (J. Am. Chem. Soc., 2011)

(untitled) - Zhong, F.; Han, X.; Wang, Y.; Lu, Y. (Angew. Chem., Int. Ed., 2011)

(untitled) - Zhang, X.-C.; Cao, S.-H.; Wei, Y.; Shi, M. (Org. Lett., 2011)

(untitled) - Deng, H.-P.; Wei, Y.; Shi, M. (Org. Lett., 2011)

(untitled) - Gu, J.; Xiao, B.-X.; Chen, Y.-R.; Li, Q.-Z.; Ouyang, Q.; Du, W.; Chen, Y.-C. (Org. Lett., 2018)

(untitled) - Mei, L.-y.; Wei, Y.; Xu, Q.; Shi, M. (Organometallics, 2013)

(untitled) - Cai, L.; Zhang, B.; Wu, G.; Song, H.; He, Z. (Chem. Commun., 2011)

(untitled) - Zhou, R.; Wang, J.; Tian, J.; He, Z. (Org. Biomol. Chem., 2012)

(untitled) - Zhou, R.; Yang, C.; Liu, Y.; Li, R.; He, Z. (J. Org. Chem., 2014)

(untitled) - Qin, Z.; Liu, W.; Wang, D.; He, Z. (J. Org. Chem., 2016)

(untitled) - Yang, C.; Chen, X.; Tang, T.; He, Z. (Org. Lett., 2016)

(untitled) - Zhu, C.-Z.; Sun, Y.-L.; Wei, Y.; Shi, M. (Adv. Synth. Catal., 2017)

(untitled) - Ramachary, D. B.; Prabhakar Reddy, T.; Suresh Kumar, A. (Org. Biomol. Chem., 2017)

(untitled) - Zhang, J.; Wu, H.-H.; Zhang, J. (Org. Lett., 2017)

(untitled) - Wang, C.; Gao, Z.; Zhou, L.; Wang, Q.; Wu, Y.; Yuan, C.; Liao, J.; Xiao, Y.; Guo, H. (Chem. Commun., 2018)

(untitled) - Zhang, X.-C.; Cao, S.-H.; Wei, Y.; Shi, M. (Chem. Commun., 2011)

(untitled) - Wang, Y.; Liu, L.; Zhang, T.; Zhong, N.-J.; Wang, D.; Chen, Y.-J. (J. Org. Chem., 2012)

(untitled) - Gomez, C.; Gicquel, M.; Carry, J.-C.; Schio, L.; Retailleau, P.; Voituriez, A.; Marinetti, A. (J. Org. Chem., 2013)

(untitled) - Hu, C.; Zhang, Q.; Huang, Y. (Chem. – Asian J., 2013)

(untitled) - Zhang, J.; Cheng, C.; Wang, D.; Miao, Z. (J. Org. Chem., 2017)

(untitled) - Chen, L.-J.; Yu, J.-H.; He, B.; Xie, J.-W.; Liu, Y.-X.; Zhu, W.-D. (J. Org. Chem., 2020)

(untitled) - Hu, F.-L.; Wei, Y.; Shi, M. (Adv. Synth. Catal., 2014)

(untitled) - Xiao, B.-X.; Jiang, B.; Song, X.; Du, W.; Chen, Y.-C. (Chem. Commun., 2019)

(untitled) - He, T.; Peng, L.; Li, S.; Hu, F.; Xie, C.; Huang, S.; Jia, S.; Qin, W.; Yan, H. (Org. Lett., 2020)

(untitled) - Han, Y.; Sheng, Y.-J.; Yan, C.-G. (Org. Lett., 2014)

(untitled) - Gong, H.; Sun, J.; Yan, C. G. (Synthesis, 2014)

(untitled) - Han, Y.; Qi, W.-J.; Shen, Y.-J.; Yan, C.-G. (Tetrahedron Lett., 2015)

(untitled) - Qi, W.-J.; Han, Y.; Yan, C.-G. (Tetrahedron, 2016)

(untitled) - Liu, C.-Z.; Han, Y.; Qi, W.-J.; Yan, C.-G. (Heterocycl. Commun., 2016)

(untitled) - Qi, W.-J.; Han, Y.; Liu, C.-Z.; Yan, C.-G. (Chin. Chem. Lett., 2017)

(untitled) - Han, Y.; Zheng, H.; Zhang, Y.-Y.; Yan, C.-G. (Chin. Chem. Lett., 2020)

(untitled) - Sun, J.; Zhang, Y.; Shi, R.-G.; Yan, C.-G. (Org. Biomol. Chem., 2019)

(untitled) - Ye, R.; Yan, C.-G. (Eur. J. Org. Chem., 2019)

(untitled) - Cao, J.; Yang, F.; Sun, J.; Huang, Y.; Yan, C.-G. (J. Org. Chem., 2019)

(untitled) - Pan, L.-N.; Sun, J.; Shi, R.-G.; Yan, C.-G. (Org. Chem. Front., 2020)

(untitled) - Zhan, S.-C.; Sun, J.; Liu, R.-Z.; Yan, C.-G. (Org. Biomol. Chem., 2020)

(untitled) - Liu, D.; Cao, J.; Sun, J.; Liu, R.-Z.; Yan, C.-G. (Org. Lett., 2020)

(untitled) - Cao, S.-H.; Zhang, X.-C.; Wei, Y.; Shi, M. (Eur. J. Org. Chem., 2011)